THE BASICS OF IDENTIFYING TRAINING NEEDS FOR HUMAN RESOURCES MANAGEMENT AND ITS IMPACT ON THE HOTEL SERVICE QUALITY (AN EXPERIMENTAL STUDY IN BABYLON HOTEL) - Khudhair Abbas Azeez Al-Quraishi, Raghad Yousif Gabraw (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims, through a theoretical and applied extension, to know the relationship and influence to determine the training and management of human resources as an independent variable to achieve the quality of hotel service as a dependent variable in the Babylon Hotel (ROTANA), in addition to know the importance and levels of dimensions of the variables that sent hotel, to work for a bundle of recommendations that contribute in evaluating work and enhance the quality of hotelservice at Babylon Hotel (ROTANA) In order to enhance and confirm the practical aspect of the study the descriptive applied approach were adopted to be completed at the level of the Babylon Hotel (ROTANA) .while the questionnaire form contained (80) paragraphs, data and information were collected from (50) respondents from the upper and middle management of the intended sample of the searched hotel, the study adopted a program with ( spss , v. 25, Amos, v.25) with the adoption of descriptive methods of statistics to test his hypotheses, The study concluded the most prominent conclusions that show the share of the hypotheses, which are embodied in the existence of a good reciprocal correlation between the training needs of human resources management and the quality of tourism service. While the results showed the necessity of increasing attention to the process of determining the training needs of the human resource management in the hotel, and there is a weakness in some dimensions of the independent variable (determining the training needs of human resources management), and Raising the level of interest in the dimensions of the responding variable (dependent) the quality of advanced hotel service.